Tertiary-butoxycarbonyl (Boc) – A strategic group for N-protection/deprotection in the synthesis of various natural/unnatural N-unprotected aminoacid cyanomethyl esters. Issue 48 (28th November 2018) - Karmakar, Ananta; Basha, Mushkin; Venkatesh Babu, G.T.; Botlagunta, Murali; Malik, Noormohamed Abdul; Rampulla, Richard; Mathur, Arvind; Gupta, Arun Kumar
Graphical abstract: Highlights: Extensively used in medicinal chemistry, as aminoacylating agents in the synthesis of aminoacyl-tRNA analogs. Used in peptide, dendrimer, buckyball amino acid, protection for carboxylic acids chemistry and resolution of amines. Achieving pure aminoacid cyanomethyl esters with an unprotected amine group remain a challenge. Here in cyanomethyl esters N -deprotection were isolated and well characterised by adequate analytical data. Abstract: A number of cyanomethyl esters of natural/unnatural aminoacids with un-protected amino functionality were synthesized because of their synthetic and medicinal importance. Critical N -Boc deprotection methods in the presence of labile (hydrolytic sensitivity) cyanomethyl functionality were screened thoroughly and it was found that readily available 4M HCl in 1, 4-dioxane solution (2–4 equiv); acetonitrile, 0 °C, 2–4 h was a suitable condition. This condition was generalized and successfully applied to a variety of alkyl, alkynyl, aryl, heteroaryl, benzyl, azido, spiro amino acid cyanomethylesters irrespective of the nature of the amine (primary or secondary) and the distance between the amine and ester group to achieve final deprotected amino esters with high yield, and purity compared to other commonly known N -protecting groups (Cbz, Fmoc, Ac, Bn, Bz etc.). It was also demonstrated that N -Boc protected aminoacid cyanomethylesters are stable enough to carry out further functionalization compared to N -unprotected counterparts.